2021
DOI: 10.3389/fphar.2021.724718
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Application of Drugs for the Treatment of Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an autoimmune and chronic inflammatory demyelinating disease of the central nervous system (CNS), which gives rise to focal lesion in CNS and cause physical disorders. Although environmental factors and susceptibility genes are reported to play a role in the pathogenesis of MS, its etiology still remains unclear. At present, there is no complete cure, but there are drugs that decelerate the progression of MS. Traditional therapies are disease-modifying drugs that control disease seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 136 publications
1
20
0
1
Order By: Relevance
“…The MMF dosage that was initially used in combination with low-dose prednisolone, according to the study design, was based on a previous work in autoimmunity (24)(25)(26). A previous study showed that even low doses of MMF (1,000 mg/d) were effective in suppressing orbital inflammation (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…The MMF dosage that was initially used in combination with low-dose prednisolone, according to the study design, was based on a previous work in autoimmunity (24)(25)(26). A previous study showed that even low doses of MMF (1,000 mg/d) were effective in suppressing orbital inflammation (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, because the etiology of MS remains largely unknown and because it is likely to be a multifactorial disease, the factors listed above could each play a role and affect immune system development and response in individuals, resulting in MS onset and disease progression. The inadequate understanding of the pathogenesis of MS makes it difficult to identify potential target molecules needed to design new therapeutic drugs [33]. Hence, a better, i.e., molecular level, understanding of what some of the factors implicated in MS might be could provide new treatment avenues.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Currently, patients with MS are treated according to clinical subtypes, i.e., CIS, RR, SP or PP. However, disease course varies greatly among patients belonging to the same clinical subtype and predicting disease trajectories from the beginning remains challenging [144]. Indeed, variable degrees of neuroinflammation and neurodegeneration affect relapse rate, disease progression and, overall, disease severity in the individual patient [145].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Currently available DMTs target neuroinflammation [144], but are not able to prevent neurodegeneration. Metabolomics and other omics approaches may reveal biochemical alterations implicated in neurodegeneration such as mitochondrial dysfunction, oxidative/nitrosative stress, dysregulation of tryptophan metabolism, and thus contribute to the development of novel medications with neuroprotective effects.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%